2020
DOI: 10.1101/2020.08.05.237677
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Common and distinct roles of frontal midline theta and occipital alpha oscillations in coding temporal intervals and spatial distances

Abstract: Judging how far something is and how long it takes to get there are critical to memory and navigation. Yet, the neural codes for spatial and temporal information remain unclear, particularly how and whether neural oscillations might be important for such codes. To address these issues, participants traveled through teleporters in a virtual town while we simultaneously recorded scalp EEG. Participants judged the distance and time spent inside the teleporter. Our findings suggest that alpha power relates to dist… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 71 publications
(116 reference statements)
0
2
0
Order By: Relevance
“…However, while similar characteristics are known for distance and time estimation, whether they are processed by shared or separate systems is still under debate. Accumulating evidence has shown that there is an asymmetric or independent relationship between the estimation of travel time and travel distance ( Brunec et al, 2017 ; Riemer et al, 2018 ; Robinson et al, 2019 ) and between their neural substrates ( Liang et al, 2020 ; Robinson & Wiener, 2021 ). At the lower levels, perception of travel time is influenced by distance, whereas perception of travel distance is not affected by time, which is consistent with the view that perception of temporal features is susceptible to spatial features, but not vice versa ( Riemer et al, 2018 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, while similar characteristics are known for distance and time estimation, whether they are processed by shared or separate systems is still under debate. Accumulating evidence has shown that there is an asymmetric or independent relationship between the estimation of travel time and travel distance ( Brunec et al, 2017 ; Riemer et al, 2018 ; Robinson et al, 2019 ) and between their neural substrates ( Liang et al, 2020 ; Robinson & Wiener, 2021 ). At the lower levels, perception of travel time is influenced by distance, whereas perception of travel distance is not affected by time, which is consistent with the view that perception of temporal features is susceptible to spatial features, but not vice versa ( Riemer et al, 2018 ).…”
mentioning
confidence: 99%
“…Furthermore, at higher levels of decision making, the distance and time to reach the reward are estimated independently in reward discounting ( Robinson et al, 2019 ). In addition, EEG studies have indicated that distance and time are processed by distinct coding schemes in terms of ERPs ( Robinson & Wiener, 2021 ) and oscillations ( Liang et al, 2020 ). These findings suggest that travel distance and travel time are closely related, but may be processed by partially separable systems.…”
mentioning
confidence: 99%